2020
DOI: 10.4178/epih.e2020004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stomach cancer: a systematic review and meta-analysis

Abstract: OBJECTIVES: This report provides information on 14 behavioral and nutritional factors that can be addressed in stomach cancer prevention programs.METHODS: PubMed, Web of Science, and Scopus were searched through December 2018. Reference lists were also screened. Observational studies addressing the associations between stomach cancer and behavioral factors were analyzed. Between-study heterogeneity was investigated using the χ<sup>2</sup>, τ<sup>2</sup>, and I<sup>2</sup> st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(172 citation statements)
references
References 29 publications
1
156
0
15
Order By: Relevance
“…For example, in a population-based prospective cohort study in which 13,957 men and 16,374 women participated, the multiple-adjusted colon cancer RR (0.78, CI = 0.49–1.22) of men consuming ≥4 times of green tea daily was lower than that of the <1 time consumers, although no significant associations between green tea consumption and colorectal cancer (CRC) risk were found in men and women [ 18 ]. However, the same search revealed that 3 studies for cervical, liver and stomach cancers did not show significant risk reduction by green tea consumption [ 23 , 24 , 25 ]. Thus, human studies found health benefits of green tea consumption in many cases, but it is also true that there are several conflicting results probably due to incomplete elimination of confounding factors.…”
Section: Anti-cancer Effects Of Green Teamentioning
confidence: 99%
“…For example, in a population-based prospective cohort study in which 13,957 men and 16,374 women participated, the multiple-adjusted colon cancer RR (0.78, CI = 0.49–1.22) of men consuming ≥4 times of green tea daily was lower than that of the <1 time consumers, although no significant associations between green tea consumption and colorectal cancer (CRC) risk were found in men and women [ 18 ]. However, the same search revealed that 3 studies for cervical, liver and stomach cancers did not show significant risk reduction by green tea consumption [ 23 , 24 , 25 ]. Thus, human studies found health benefits of green tea consumption in many cases, but it is also true that there are several conflicting results probably due to incomplete elimination of confounding factors.…”
Section: Anti-cancer Effects Of Green Teamentioning
confidence: 99%
“…Dietary factors may play an important role in the pathogenesis of gastric carcinoma. [ 16 ] Low intake of fresh fruits and vegetables, high-salt diet, poorly preserved food, excess alcohol intake, and obesity may be associated with an increased risk of gastric carcinoma. [ 17 ] Recent studies tried to verify the possible ameliorative effect of fresh fruits and vegetables rich in beta carotenes, vitamin C, vitamin D, and tocopherols on gastric carcinogenesis.…”
Section: Risk Factors Of Gastric Carcinomamentioning
confidence: 99%
“…[ 11 ] Besides, the risk of developing gastric carcinoma may be up to 2–3 folds in patients with a positive family history of gastric carcinoma compared to persons with negative family history for this type of cancer. [ 16 ]…”
Section: Risk Factors Of Gastric Carcinomamentioning
confidence: 99%
“…In 2017, according to the Korea Central Cancer Registry (KCCR), the ageadjusted incidence rate of GC was 32.0 per 100,000 in the overall population, 46.4 per 100,000 in men, and 19.6 per 100,000 in women [3]. Various epidemiological studies have demonstrated that smoking [4][5][6][7], alcohol consumption [4,5,8], obesity and physical inactivity [4,5,9], family history of GC [10][11][12][13][14] and numerous dietary factors such as foods preserved with salts, pickled vegetables, low fruits and vegetables consumption, low dietary vitamin C and carotenoid intake, high salt consumption, high processed meat consumption, high salt intake [4,5,15,16] are associated with the increased risk of GC.…”
Section: Introductionmentioning
confidence: 99%